The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Beyond the superordinate categories of “Gay Men” and “Lesbian Women”: Identification of gay and lesbian subgroups - McCutcheon, Jessica M.; Morrison, Melanie A. (Journal of Homosexuality, 2021)
Nation-wide opinion polls and social scientific studies indicate that evaluations of gay men and lesbian women have become increasingly favourable. These positive trends do not explain the widespread discrimination experiences being reported. To assist researchers in investigating attitudes towards gay and lesbian persons, the current research examines whether there are multiple “types” that are identifiable and salient. Two Canadian studies (Ns = 67 and 206) were conducted to establish the presence of gay and lesbian subgroups. Using subgroups generated by Study 1 participants, community and student sub-samples selected those they perceive to exist. Results indicated that, for gay men, the subgroups Drag Queen and Flamboyant emerged, as did Butch for lesbian women. Amongst students, Closeted and Feminine also emerged for gay men, as well as Feminist and Tomboy for lesbian women. These findings have implications for contemporary research on gay- and lesbian-related attitudes and the methodology used to assess them.
Keywords: amériques; canada; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines